KUALITAS LINGKUNGAN DAN AKTIVITAS ENZIM PENCERNAAN UDANG VANNAMEI (Litopenaeus vannamei) PADA BERBAGAI KONSENTRASI PROBIOTIK BIOREMEDIASI-Bacillus sp. - Siti Aslamyah (Fish Scientiae, 2019)
Bioremediation-Bacillus sp. probiotics with the composition of the beneficial bacteria, as well as working synergistically on aquaculture and environment in the host gastrointestinal tract. In addition, it can improve the quality of the environment can also increase the activity of digestive enzymes shrimp. Ultimately lead to increased growth and minimize the risk of disease of shrimp. The purpose of this study to determine the optimum concentration of applications Bioremediation-Bacillussp. probiotics vannamei shrimp culture in the media. The study was designed in a Completely Randomized Design (CRD) with 4 treatment concentration of bioremediation-Bacillus sp. probiotics the control (without probiotic), 0.5; 1.0, 1.5 ppmper week, with three replications each. During the study, the test shrimp rearing in glass aquaria with a capacity of 30 L with a density of 4 fish / L and fed the form of powder with 52% protein content as much as 70-100% of total biomass. Watermedium used ± 30 ppt salinity as much as 25 L. The results showed improvement of environmental quality cultivation occurs in the probiotic treatment applications, particularly ammonia levels lower than controls. Digestive enzyme levels of Į-amylase and protease also increased significantly compared to controls. This condition which cause the vannamei shrimp survival and growth were receiving higher than controls of probiotic treatment, while various concentrations of probiotic did not produce differences in response. Application of Bioremediation-Bacillus sp.probiotics can be concluded with a concentration of 0.5 ppm per week in culturemedia can improve the quality of the environment cultivation and the activity ofdigestive enzymes Į-amylase and protease, thus increasing the survival and growthof vannamei shrimp.